Evolutionary history of the C-repeat binding factor/dehydration-responsive element-binding 1 (CBF/DREB1) protein family in 43 plant species and characterization of CBF/DREB1 proteins in Solanum tuberosum - Li, Wan; Chen, Yue; Ye, Minghui; Lu, Haibin; Wang, Dongdong; Chen, Qin (BMC ecology and evolution, 2020)
Plants are easily affected by temperature variations, and high temperature (heat stress) and low temperature (cold stress) will lead to poor plant development and reduce crop yields. Therefore, it is very important to identify resistance genes for improving the ability of plants to resist heat stress or cold stress by using modern biotechnology. Members of the C-repeat binding factor/Dehydration responsive element-binding 1 (CBF/DREB1) protein family are related to the stress resistance of many plant species. These proteins affect the growth and development of plants and play vital roles during environmental stress (cold, heat, drought, salt, etc.). In this study, we identified CBF/DREB1 genes from 43 plant species (including algae, moss, ferns, gymnosperms, angiosperms) by using bioinformatic methods to clarify the characteristics of the CBF/DREB1 protein family members and their functions in potato under heat and cold stresses. In this study, we identified 292 CBF/DREB1 proteins from 43 plant species. However, no CBF/DREB1 protein was found in algae, moss, ferns, or gymnosperms; members of this protein family exist only in angiosperms. Phylogenetic analysis of all the CBF/DREB1 proteins revealed five independent groups. Among them, the genes of group I do not exist in eudicots and are found only in monocots, indicating that these genes have a special effect on monocots. The analysis of motifs, gene duplication events, and the expression data from the PGSC website revealed the gene structures, evolutionary relationships, and expression patterns of the CBF/DREB1 proteins. In addition, analysis of the transcript levels of the 8 CBF/DREB1 genes in potato (Solanum tuberosum) under low-temperature and high-temperature stresses showed that these genes were related to temperature stresses. In particular, the expression levels of StCBF3 and StCBF4 in the leaves, stems, and roots significantly increased under high-temperature conditions, which suggested that StCBF3 and StCBF4 may be closely related to heat tolerance in potato. Overall, members of the CBF/DREB1 protein family exist only in angiosperms and plays an important role in the growth and development of plants. In addition, the CBF/DREB1 protein family is related to the heat and cold resistance of potato. Our research revealed the evolution of the CBF/DREB1 family, and is useful for studying the precise functions of the CBF/DREB1 proteins when the plants are developing and are under temperature stress.